Interpreting motion : grounded representations for spatial language - Mani, Inderjeet; Pustejovsky, J. (James) (Oxford : Oxford University Press, 2012)
This text shows how language structures constrain concepts of motion, analysing the semantics of motion expressions in a range contexts from route navigation to textual description. It is written for a broad audience including linguists, cognitive and computer scientists, and those working in GIS and artificial intelligence.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Semantics; Motion in language